PANDEMIC AT THE POLLS: AN ANALYSIS OF THE DECISION TO CONTINUE THE 2020 REGIONAL HEAD ELECTION IN THE NEW NORMAL ERA - Ratna Rosanti (Jurnal Ilmiah Dinamika Sosial, 2020)
This article will specifically provide a preliminary assessment of the many risks that the Covid-19 pandemic might pose if elections continue to be held and it is not impossible that elections continued during the pandemic will be far from being fair, honest and transparent even endangering the security and safety of voters at the Polling Stations. The emergence of a new era during the pandemic called New Normal where everyone must behave new in everyday life by prioritizing aspects of health will certainly have a significant influence in the implementation of elections. The method used is the study of literature. The literature used in this study includes all literature, news coverage and reports relating to the holding of the elections including previous books and articles that discuss the holding of elections during a pandemic. This paper begins by explaining why elections are an important part of democracy, and then looks at how the government's response to the pandemic and elections that will be held in the New Normal era will present significant solutions about the future of democracy itself. In this paper, the author also recommends several things related to the holding of elections during the pandemic. The main findings of this paper are: First, the presence of the virus itself can directly prevent voters from casting their votes at the polling stations and even affect the overall level of voter participation. Second, there are consequences of formally delaying the holding of elections which vary by type of regime (national or local). Third, some elements in the electoral cycle can be affected by the pandemic.